Challenges and adaptation strategies for improving quality and biochemical changes of Flame Seedless grapevines in Mediterranean environment under increasing climate variability - Alebidi, Abdullah; Abd El-Gawad, Mahmoud G.; Elmenofy, Hayam M.; Galal, Hoda; Rihan, Hail Z.; Abdel-Sattar, Mahmoud (Frontiers in Plant Science, 2026)
Grapevine cultivation in a Mediterranean environment is significantly influenced by climate conditions, which determine vine growth characteristics and berry quality, resulting in financial losses for growers. To address these issues and meet the export standards of Flame Seedless grapes, integrated strategies were adopted, including plastic covering along with foliar applications of 24-epibrassinosteroids and gibberellic acid. A split-plot experiment was conducted in 2024 and 2025, testing two gibberellic acid (GA3) regimes (one at 110 µL L−1 [ppm] applied at three stages and another at 20 µL L−1 applied at two stages), alongside various concentrations of foliar-applied brassinosteroid (BR) at 0, 0.5, 1.0, 1.5, and 2.0 µL L−1. The results indicated that the application of GA3 and/or 24-epibrassinosteroids significantly improved the quality of grape clusters and berries, including their chemical traits, color parameters, and the biochemical composition of grape leaves. Specifically, 20 µL L−1 GA3 enhanced berry firmness, berry adherence strength, coloration, and optimized total soluble solids (TSS), sugar, and anthocyanin levels, while decreasing the number of small berries, weight loss %, and titratable acidity. Meanwhile, the combined treatment of GA3 at 20 µL L−1 + BR at 2.0 µL L−1 treatment µL L−1 significantly increased cluster weight, cluster length, shoulder length, berry weight, berry diameter, berry force, berry firmness, CIRG, TSS, TSS/acidity ratio, total sugars, reducing sugars, and anthocyanin, while decreasing small berry incidence and acidity. The combination of GA3 at 20 µL L−1 with BR at 2.0 µL L−1 yielded the most significant improvements in berry and cluster dimensions and color intensity, as well as in the oxidative burst and antioxidant defense enzymes of fresh grape leaves. Overall, the results highlight that BR can be used as a partial substitute for GA3 under plastic covering as a promising tool to facilitate early harvest, improve grape bunch quality and berry quality, and reduce postharvest losses.